Facile and low‐cost fabrication of uniform silicon micro/nanostructures by nanopitting‐assisted wet chemical etching. (1st September 2018) - Wang, Feng; Jiang, Shulan; Han, Jinghui; Guo, Guangran; Yu, Bingjun; Yang, Weiqing; Qian, Linmao
Abstract : Silicon micro/nanostructures are promising building blocks for high‐performance solar cells, lithium‐ion batteries, sensors and so on. Great challenges like high cost and complex fabrication process still exist for the fabrication of silicon micro/nanostructures, especially for the fabrication of uniformly distributed silicon micro/nanostructures. In this study, the generally unwelcome failure of materials, nanopitting, was introduced and demonstrated to be effective in micro/nanofabrication for the first time. Together with wet chemical etching, uniformly distributed silicon micro/nanostructures were obtained. Ag islands were formed by the nanopitting of chloridion, which will be used as mask and catalyser in the chemical etching process. The silicon micro/nanostructures, especially, uniformly distributed p‐type silicon micro/nanostructures were fabricated with the low‐cost and facile fabrication approach. In addition, the application of the silicon micro/nanostructures was demonstrated as microsupercapacitive electrodes with the integration of MnO2 nanostructures. The results show that the electrochemical performance of silicon micro/nanostructures was much better than that of silicon microstructures. The proposed approach is cost‐effective to fabricate silicon micro/nanostructures, and the silicon micro/nanostructures have great potentials in miniaturised energy storage devices, sensors and photodevices.